The Effect of Career Planning and Self-Efficacy on Work Readiness of Final Year Students - Anggi Eka Mentari; Musoli Musoli (Journal of Innovation, Business Management and Entrepreneurship, 2025)
Human resources (HR) must play an active and dominant role in every organizational activity in order to answer all challenges in the future. In addition, they must also be ready and able to compete, therefore they are planners, actors and determinants of the realization of organizational goals. This study aims to examine the effect of Career Planning and Self Efficacy partially and simultaneously on the Work Readiness of Final-Year Students. The researcher used a quantitative descriptive research method with samples from final-year students at the Muhammadiyah - 'Aisyiyah University in Yogyakarta. The sampling was done by purposive sampling technique which got 165 respondents. The researcher used a questionnaire to collect data and then processed it with Multiple Linear Regression Analysis. From the results of the study, it was found that there was a positive and significant partial effect between the Career Planning variable (XI) on the Job Readiness variable (Y), there was a positive and significant partial effect between the Self Efficacy Variable (X2) on the Job Readiness variable (Y) and there is a positive and significant simultaneous effect between Career Planning (XI), Self-Efficacy (X2) variables on Work Readiness (Y).